Lipid phosphate phosphatases dimerise, but this interaction is not required for in vivo activity - Burnett, Camilla (BioMed Central, 2004)
BACKGROUND: Lipid phosphate phosphatases (LPPs) are integral membrane proteins believed to dephosphorylate bioactive lipid messengers, so modifying or attenuating their activities. Wunen, a Drosophila LPP homologue, has been shown to play a pivotal role in primordial germ cell (PGC) migration and survival during embryogenesis. It has been hypothesised that LPPs may form oligomeric complexes, and may even function as hexamers. We were interested in exploring this possibility, to confirm whether LPPs can oligomerise, and if they do, whether oligomerisation is required for either in vitro or in vivo activity. RESULTS: We present evidence that Wunen dimerises, that these associations require the last thirty-five C-terminal amino-acids and depend upon the presence of an intact catalytic site. Expression of a truncated, monomeric form of Wunen in Drosophila embryos results in perturbation of germ cell migration and germ cell loss, as observed for full-length Wunen. We also observed that murine LPP-1 and human LPP-3 can also form associations, but do not form interactions with Wunen or each other. Furthermore, Wunen does not form dimers with its closely related counterpart Wunen-2. Finally we discovered that addition of a trimeric myc tag to the C-terminus of Wunen does not prevent dimerisation or in vitro activity, but does prevent activity in vivo. CONCLUSION: LPPs do form complexes, but these do not seem to be specifically required for activity either in vitro or in vivo. Since neither dimerisation nor the C-terminus seem to be involved in substrate recognition, they may instead confer structural or functional stability through dimerisation. The results indicate that the associations we see are highly specific and occur only between monomers of the same protein.